Effects of Moringa oleifera in Two Independents Formulation and as Neuroprotective Agent Against Scopolamine-Induced Memory Impairment in Mice - Arozal, Wawaimuli; Purwoningsih, Emni; Lee, Hee Jae; Barinda, Agian Jeffilano; Munim, Abdul (Frontiers in Nutrition, 2022)
Background: The cognitive deficit has frequently been found in the elderly population. Several studies showed that every single part of Moringa oleifera, including leaves, roots, and seeds, has abundant micronutrients, including flavonoids, which improve neurobehavioral capacity. However, which herb parts display optimal neuropharmacological properties are remains unknown. Objective: We investigate whether M.oleifera seed oil (MOO) or aqueous M.oleifera leaves extracts (MOE) may ameliorate memory impairment in mice induced with scopolamine. Additionally, the phytochemical analyses of those two independent formulations were also be analyzed. Methods: two ml/kg BW of MOO and 500 mg/kg BW of MOE were orally administered to the mice for 28 days, followed by intraperitoneal injection of scopolamine (1 mg/kg) at the day 22 to 28 to induce cognitive impairment in those mice. Results: The scopolamine (Sco) group showed memory retention impairment represented by the Y-maze and novel object recognition tests, significant enhancement of acetylcholine esterase (AChE) activity in hippocampus tissue (P<0.0001), and increased the level of total antioxidant capacity (TAOC) in serum. Interestingly, the Sco-induced memory defect was improved, and completely blunted the AChE exacerbation in Sco+MOO-treated mice (P<0.0001), although the TAOC level was comparable among the groups. Mechanistically, both Tropomyosin receptor kinase B (TrkB), as a Brain-derived neurotrophic factor receptor, and nuclear factor-kappa-light-chain-enhancer of activated B cells (NF-B) protein expressions were enhanced win the hippocampus isolated from the Sco group. Nonetheless, Pretreatment with MOO only, but not MOE, ameliorated the enhanced protein expression levels of TrkB and NF-B (P<0.05 and P=0.09, respectively). Conclusion: Our data reveal that MOO is preferable than MOE as a neuroprotective as evidence by improve the memory impairment. This effect, at least in part, through inhibiting the AChE and NF-κB activities and modulating the TrkB expression level.